PELATIHAN RANUP HIASAN HANTARAN SEBAGAI UPAYA PELESTARIAN BUDAYA ACEH DI GAMPONG BLANG PULO, KECAMATAN MUARA SATU, KOTA LHOKSEUMAWE - Meliza, Richa; Harinawati, Harinawati; Rizki, Aflia; Arifin, Awaludin (Universitas Malikussaleh, 2023)
The PKK women's group is the most effective and efficient forum for providing training or in other words providing in-depth knowledge related to cultural preservation, especially Acehnese culture. Culture will be preserved and developed if we continue to hone our abilities in studying and understanding these customs. In fact, the cultural potential of a particular area can survive or experience change depending on the people. So far, some people think that culture can only increase the development of a region, even though if we know and study culture it can develop along with the times without leaving behind the uniqueness of a culture or customs such as the ranup hantaran in Acehnese wedding customs which is one that is mandatory for every person. Acehnese wedding event. Because ranup is a very vital medium in connecting symbolic communication between the two parties or the bride and groom, from the start of an event until the party ends. And most importantly, ranuh is a symbol of glory in glorifying the guests of